(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Information retrieval became an independent research region from a standard database management system more significant than a decade earlier. This was steered by the raising useful demands that present-day total content search engines need to satisfy. Existing database management systems are not with the ability to assist such flexibility. With the rise of records to become cataloged and fetched and also the hefty improving amount of work, modern-day search engines struggle with Scalability, integrity, distribution, and performance problems. Information access became a proper analysis place from a typical database management system more than many years earlier. This was driven due to the useful boosting demands that modern complete content search engines need to fulfill. Current database management systems are certainly not efficient in assisting such adaptability. Along with the boost of information to become listed and also recovered and the massive boosting work, the contemporary online search engine has to deal with Scalability, reliability, distribution as well as functionality troubles. This paper deals with integrating information from heterogeneous data sources and row level security.